Diplomasi Kopi: Kebijakan Luar Negeri Indonesia dalam Meningkatkan Kerjasama Ekspor Komoditas Kopi ke Amerika Serikat - Shertina, Rara (Global and Policy Journal of International Relations, 2019)
ABSTRACTIndonesia's potential as the top five coffee producers and exporters in the world will create opportunities in order to meet the high demand of US coffee consumption. However, competition for the world coffee export commodity market in the United States is very competitive. Indonesia launched a foreign policy on coffee diplomacy that involved a variety of stakeholders to increase Indonesia's coffee exports to the United States and give branding to Indonesian specialty coffee. The author aims to show the success of coffee diplomacy in the United States-Indonesia coffee commodity export cooperation seen by the increase in exports from year to year. The author uses descriptive-analytical methods to provide an overview of Indonesian coffee exports to the United States. Therefore, it easier for readers to obtain information about coffee diplomacy analysis which is motivated by several determinants of Indonesian foreign policy and national interests contained in legal instruments. Analysis of the coffee diplomacy policy also involves historical, cultural and political aspects to explain the flow of foreign policy formulation from domestic factors.Keywords: Coffee, Bilateral Cooperation, Coffee Diplomacy, Indonesia, United States DOI : https://doi.org/10.33005/jgp.v7i02.1830